2019
DOI: 10.1038/s41598-019-45524-1
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in humans drinking tube well water with high levels of iron in arsenic–polluted area

Abstract: Well water for drinking with increased levels of iron in arsenic-polluted areas has been reported worldwide. Oral exposure to arsenic has been shown to be associated with hearing loss, while there is no evidence for an association between excessive exposure to iron and hearing loss in humans. In this study, we determined iron and arsenic levels in biological samples and hearing levels by pure tone audiometry (PTA) in subjects in a control area and an arsenic-polluted area in Bangladesh. The iron level in well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…It enhanced our understanding of the data and provided a more precise basis for scientific insight. This study covered 15 studies published between 2009 and 2022, 11 of which were conducted in Asia (Japan, 6,11,12 Korea, 3,9,13,14 and China 5,7,15,16 ) and 4 in the United States. 4,[17][18][19] Of these studies, 10 articles identified lead and cadmium as the main or one of the risk factors for HL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It enhanced our understanding of the data and provided a more precise basis for scientific insight. This study covered 15 studies published between 2009 and 2022, 11 of which were conducted in Asia (Japan, 6,11,12 Korea, 3,9,13,14 and China 5,7,15,16 ) and 4 in the United States. 4,[17][18][19] Of these studies, 10 articles identified lead and cadmium as the main or one of the risk factors for HL.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous research has reported a plausible link between environmental exposure to heavy metals and the risk of HL, with a particular emphasis on the ototoxic effects of lead, cadmium, arsenic, and mercury. [3][4][5][6] Studies have indicated a potential association between lead exposure and an increased risk of HL, particularly among children. 7 Animal models have demonstrated that lead exposure can impair axonal transport and suppress auditory processing near the cochlea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are less pathogenic microbes in well water than in lake or pond water, the use of well water as drinking water has been accelerating in developing countries. Unfortunately, however, many kinds of disorders caused by toxic elements in well drinking water (element-originating diseases) have been reported in developing countries [1][2][3][4][5]. It is our urgent task to resolve the global issues that are directly associated with human life.…”
Section: Introductionmentioning
confidence: 99%
“…As the second step, human studies including epidemiological [14][15][16] and clinical [17][18][19][20][21] studies are generally indispensable for assessing the risks of environmental factors including toxic elements for various diseases. Partial clarification of the mechanisms underlying the development of diseases is possible by analyses of human samples and physiological examinations in addition to questionnaires [2,4,5,[14][15][16][17][18][19][20][21][22]. However, there is an ethical limitation for detailed analysis of the mechanisms underlying the development of elementoriginating diseases in epidemiological and clinical studies.…”
Section: Introductionmentioning
confidence: 99%